Ethical considerations in the design, execution, and analysis of clinical trials of chronic pain treatments. (May 2019) - Rowbotham, Michael C.; McDermott, Michael P.
Abstract: Introduction: In the field of pain research, clinical trials may randomize over 500 subjects and include more than 150 sites spanning over a dozen countries. Methods: This review examines the ethical considerations affecting clinical trial design, execution, and analysis of trials for chronic pain. The Belmont Report has been the touchstone for human studies protection efforts since 1979. Commissioned by the U.S. government in response to ethical failures in medical research, such as the Tuskegee Syphilis Study, the report emphasizes 3 basic principles: respect for persons, beneficence, and justice. Trial design and sample size have important ethical implications. Conclusions: Measures to enhance trial transparency and combat publication and many other types of bias should be implemented.